Ecological Recovery and Resilience in Environmental Risk Assessments at the European Food Safety Authority. (17th August 2018) - Brock, Theo; Bigler, Franz; Frampton, Geoff; Hogstrand, Christer; Luttik, Robert; Martin‐Laurent, Fabrice; Topping, Christopher John; van der Werf, Wopke; Rortais, Agnes
ABSTRACT: A conceptual framework was developed by a working group of the Scientific Committee of the European Food Safety Authority (EFSA) to guide risk assessors and risk managers on when and how to integrate ecological recovery and resilience assessments into environmental risk assessments (ERA). In this commentary we advocate that a systems approach is required to integrate the diversity of ecosystem services (ES) providing units, environmental factors, scales, and stressor‐related responses necessary to address the context dependency of recovery and resilience in agricultural landscapes. A future challenge in the resilience assessment remains to identify the relevant bundles of ecosystem services provided by different types of agroecosystem that need to be assessed in concert. Integr Environ Assess Manag 2018;14:586–591. © 2018 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: We define ecological resilience as the capacity of an ecosystem to return, after a stress event, to its original or an alternative operating range of ecosystem services (ES) delivery; this is intrinsically linked to structural and functional recovery of populations that support ES. Variation in species traits, landscape properties, and exposure characteristics determine the potential for ES providing units to escape stress events in space and time. Environmental risk assessment (ERA) requires a systems approach to address effects on, and recovery of, ES delivery as an assessment endpoint for resilience. Challenges in ERA are to identify the bundles of ES provided by different types of (agro‐) ecosystem, to collect information on the normal operating range of relevant ES providing units, and to define ecological production functions that enable a quantitative linkage of measurement endpoints to the delivery of key ES valued by society.